Influence of the Institutional Environment on the Processes of International Labor Migration to the Regions of the Russian Federation - Mukhametov, Ruslan S. (Regionologiâ, 2025)
Introduction. The relevance of the research topic is determined by the increasing role of international labor migration in the socio-economic development of Russian regions and the need for effective management of migrant flows. In the conditions of demographic decline and labor shortage, the attraction of foreign migrants becomes an important factor of economic growth. The study of the determinants of international labor migration has often focused on the socio-economic characteristics of destinations. This article examines the impact of the quality of public administration of territories on their ability to attract labor immigrants. Materials and Methods. The empirical basis of the study was the data of Rosstat, as well as information from the Atlas “Islamic Community of the Russian Federation”. The research method was regression analysis of panel data (fixed effects model). Results. Statistical processing of the data showed that the constituent entities of the Russian Federation with a higher quality of state governance attract more international labor migrants. At the same time, most socio-economic factors that are traditionally used to explain the attractiveness of the destination territory were not confirmed, although they are indirectly included in the category of “state capacity”. Regression analysis demonstrated a positive impact of the share of Muslim population in the Russian regions on the number (in relative terms) of foreign labor migrants. The concept of “ethnic networks” has not been empirically tested. Discussion and Conclusion. International labor migrants prefer to come to destination territories with a higher quality of public administration. At the same time, it is important to ensure social integration of immigrants and protection of their rights in order to avoid problems in the host society that are related to socio-cultural differences. The results of the study can contribute to the growth of the efficiency of migration management at the national and sub-national levels, as well as allow forecasting the directions of migration flow.